Development of Abrasives from Non-woven Based on Used Textiles. Issue 6 (3rd June 2022) - Elaissi, Arwa; Alibi, Hamza; Jabli, Mahjoub; Ghith, Adel
ABSTRACT: In this paper, the development of a new composite as an abrasive material was reported. The composite was constituted of iron shavings as grains, a prepared non-woven from cellulosic fibers waste as support and a polyurethane resin as matrix. The studied composite was investigated using FT-IR spectroscopy and SEM analyses. FT-IR data confirmed that the non-woven composite was composed of cellulosic fibers and iron. SEM photos indicated that the resin was distributed on the surface of the composite and the iron grains were strongly fixed. The properties of the prepared composites were evaluated and compared with some commercial abrasives. The effect of some chemical modifications on the non-woven characteristics and on the lifetime of the prepared abrasives was studied. The concentration of the resin on the lifetime of abrasives was also discussed. The results showed that the composites made with polyurethane resin had longer life compared to some commercial abrasives. Chemically modified non-woven supports exhibited better results compared to untreated non-woven supports.